If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + 12 = 45 Reorder the terms: 12 + 11y = 45 Solving 12 + 11y = 45 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 11y = 45 + -12 Combine like terms: 12 + -12 = 0 0 + 11y = 45 + -12 11y = 45 + -12 Combine like terms: 45 + -12 = 33 11y = 33 Divide each side by '11'. y = 3 Simplifying y = 3
| Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 | | 8k-8=24 | | 1.5a=-12 | | -5.9=w+6.1 | | 9x+-9+9x= | | f(x-3)=5x^2-x-8 | | F(x)=5x^2+6x-8 | | -10.6x+5.6x=40 | | 18x-10-6w=50 | | -5(3d+8)=35 | | -4m+2-4m+12= | | 4(u-9)= | | F(x)=5(90)-100 | | 75=5(x)-100 | | =(3x^3-7x^2+5x-9)-(7x^3-7x^2-4x+4) | | F(x)=5(75)-100 | | 4x-4-7x-10= | | 100=5(x)-100 | | 7U+5U=2U+30 | | F(x)=5(65)-100 | | K(3)=39+-2 | | x-1-Ln(x)=0 | | 16x-19y=24 |